The model of Big Data analysis for MICE using IoT (beacon) and artificial intelligence service (recommendation, interest, and movement) - Kim, Sunghyun; Park, Sungbum; Kang, Jangmook; Lee, Sangwon (International Journal of Engineering and Technology, 2018)
The aim of this research is to design and construct Smart Exhibition Convention service that utilizes IoT based Big Data. First, we designed the Total Smart MICE platform that can be used from the beginning to the end of the exhibition. In addition, we added support to enhance the competitiveness of objective and valuable reference model-based display tasks (planning, sales, etc.). In addition, we have developed new businesses and smart services utilizing the implications of data analysis. To improve the value of data collection and utilization, we hope that this research model will spread to the platform industry. The results of the study will be an opportunity to transform the paradigm of the exhibition industry to a smart MICE platform.Â Â